A new set of microsatellite loci for Cattleya walkeriana Gardner, an endangered tropical orchid species and its transferability to Cattleya loddigesii Lindl. and Cattleya nobilior Reichenbach - Rossini, Bruno C. [UNESP]; Kampa, Mariá B.; Marino, Celso L. [UNESP]; Pereira, Fernanda Bortolanza [UNESP]; Alves, Fábio M.; Pereira De Souza, Anete; Ibanes, Bruna; Schwarcz, Kaiser Dias; Zucchi, Maria Imaculada; Bobrowski, Rogério; Peres, Fabiana S. B.; Tambarussi, Evandro Vagner [UNESP] (Cambridge University Press (CUP), 2018)
In this study, we isolate and analyse a new set of microsatellite loci for Cattleya walkeriana. Twenty-two primer pairs were screened for C. walkeriana (n = 32) and assessed for their transferability to Cattleya loddigesii (n = 12) and Cattleya nobilior (n = 06). All loci amplified for C. walkeriana; however, for C. loddigesii and C. nobilior, four and five primers, respectively, did not present amplification. The polymorphic loci presented between 2 and 13 alleles per locus for both C. walkeriana and C. loddigesii, with respective averages of 5.1 and 4.2. For C. nobilior, we found between two and five alleles per locus, with an average of 2.6. For C. walkeriana, observed heterozygosity varied from 0.100 to 0.966, whereas expected heterozygosity ranged from 0.097 to 0.900. The observed and expected heterozygosity for C. loddigesii and C. nobilior were also estimated. We found no significant linkage disequilibrium between any pair of loci, and evidence of null alleles at four loci (Cw16, Cw24, Cw30 and Cw31) for C. walkeriana. The combined power to exclude the first parent and combined non-exclusion probability of identity were 0.999 and 2.3 × 10-20, respectively. These new loci can be used in studies of germplasm resources, and assessments of genotypic and genetic diversity and population structure, thus improving the accuracy of such analyses and their applicability in the conservation and protection of these endangered species.
Keywords: Brazilian orchid; conservation genetics; hybridization; population genetics; tropical orchid species